AI-BASED HUMAN CAPITAL AS A CATALYST FOR INCREASING THE STRATEGIC AGILITY OF EDUCATIONAL ORGANIZATIONS - Kusumawati, Ida; Rahman, Muthi'ah; Tri Ananda Dewi, Annisa; Hikmah, Uryatul; Khofsah, Siti; Haisuma Kunta, Ittaqillah; Hasan Agus R, Abu (International Journal of Multidisciplinary Reseach, 2025)
The development of AI technology is able to invite educational organizations to continue to learn and develop the capacity of human capital, so that they are able to adapt to changes in the world. The purpose of this research is to explain the role of AI-based human capital as a catalyst to improve and increase the strategic agility of an educational organization. Through descriptive analysis and literature review, the implementation of human capital management and development is able to strengthen educational organizations by responding to changes quickly, making data-based decisions, and fostering innovation. AI also plays a role in personalizing learning, improving human capital competence, and process efficiency. How to maximize these benefits? It is necessary to develop an adaptive culture, digital literacy, and strengthen infrastructure and policies. The results of this study explain that the synergy between AI and human capital capacity is important in increasing the strategic agility of educational organizations to answer challenges in the current era.